Identificação da dependência do CCR4 para o recrutamento de células dendríticas produtoras de TNF-α e NOS2 mediando a patogênese da síndrome respiratória aguda associada à malária - Bruno Galvão Filho (2018)
Malaria-associated acute respiratory distress syndrome (MA-ARDS) and acute lung injury (ALI) are complications that cause lung damage and often leads to death. The MA-ALI/ARDS is associated with a Type 1 inflammatory response mediated by T lymphocytes and IFN-γ. Here, we used the Plasmodium berghei NK65 (PbN)-induced MA-ARDS model that resemble human disease and confirmed that lung CD4+ and CD8+ T cells predominantly expressed T-bet and IFN-γ. Surprisingly, we found that development of MA-ARDS was dependent on functional CCR4, which normally mediates recruitment of Th2 lymphocytes and regulatory T cells. In this Type 1 inflammation-ARDS model, we found that CCR4 was not involved in recruitment of T lymphocytes, but required for the emergence of TNF-α/iNOS producing dendritic cells (TipDCs) in the lungs. In contrast, recruitment of Tip-DCs and development of MA-ARDS was unaffected significantly in CCR2-/- mice infected with PbNK65. Importantly, we showed that NOS2-/- mice are resistant to PbNK65-induced lung damage, indicating that nitric oxide produced by TipDCs is an essential component of MA-ARDS pathology. Lastly, our experiments demonstrate that local production of IFN-γ by CD8+ cells in the lungs is responsible for inducing iNOS and TNF-α producing DCs activity in this MA-ARDS model.